2022
DOI: 10.14202/vetworld.2022.324-330
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dietary supplementary probiotics as substitutes for antibiotic growth promoters during the starter period on growth performances, carcass traits, and immune organs of male layer chicken

Abstract: Background and Aim: With the increased concerns about global protein supply, chicken meat, especially from male layer chicken, constitutes an alternative in terms of quality and carcass traits. Probiotics have been proposed for replacing antibiotic growth promoters (AGPs), which have been prohibited as poultry supplement feeds. The present study aimed to determine the efficacy of dietary supplementary probiotics during the starter period on growth performances, carcass traits, and immune organs of male layer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This study is in accordance with Agustono et al . [ 36 ], in which probiotics ( L. acidophilus , Lactobacillus plantarum , and Bifidobacterium spp.) with 1.2 × 10 9 concentration colony-forming units/mL showed positive results on growth performance (body weight, feed consumption, feed conversion ratio, carcass weight, and breast meat weight).…”
Section: Discussionmentioning
confidence: 99%
“…This study is in accordance with Agustono et al . [ 36 ], in which probiotics ( L. acidophilus , Lactobacillus plantarum , and Bifidobacterium spp.) with 1.2 × 10 9 concentration colony-forming units/mL showed positive results on growth performance (body weight, feed consumption, feed conversion ratio, carcass weight, and breast meat weight).…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are live microorganisms that promote the growth of beneficial bacteria, modify the structure of intestinal microorganisms, and substantially contribute to animal health ( Vilà et al , 2010 ; Morelli and Capurso, 2012 ). In recent years, several studies have confirmed that developing green alternatives to antibiotics can solve various intestinal problems and maintain the balance of intestinal microorganisms, ultimately improving the health and production performance of poultry ( Xiao et al , 2021 ; Agustono et al , 2022 ; Kulkarni et al. , 2022 ; Luise et al , 2022 ).…”
Section: Beneficial Properties and Applications Of Probiotics In Chic...mentioning
confidence: 99%
“…These are live microbial feed supplements that can improve nutrient absorption, increase productivity, reduce chick mortality, and stimulate immunity ( Park et al, 2016 ). In this regard, few studies demonstrated the potential for dietary supplementation of probiotics in day-old chicks on improving growth in pullets and performance in adult layers ( Aksu et al, 2005 ; Agustono et al, 2022 ; Hahn-Didde and Purdum, 2016 ). Although most studies have focused on the effect of in-feed probiotic supplementation on layer growth and performance, optimum embryonic growth is critical to posthatch growth and performance ( Walstra et al, 2010 ; Willems et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%